Can switchgrass increase carbon accrual in marginal soils? The importance of site selection. Issue 2 (6th December 2020) - Kasanke, Christopher P.; Zhao, Qian; Bell, Sheryl; Thompson, Allison M.; Hofmockel, Kirsten S.
Abstract: Most soil carbon (C) is in the form of soil organic matter (SOM), the composition of which is controlled by the plant–microbe–soil continuum. The extent to which plant and microbial inputs contribute to persistent SOM has been linked to edaphic properties such as mineralogy and aggregation. However, it is unknown how variation in plant inputs, microbial community structure, and soil physical and chemical attributes interact to influence the chemical classes that comprise SOM pools. We used two long‐term biofuel feedstock field experiments to test the influence of cropping systems (corn and switchgrass) and soil characteristics (sandy and silty loams) on microbial selection and SOM chemistry. Cropping system had a strong influence on water‐extractable organic C chemistry with perennial switchgrass generally having a higher chemical richness than the annual corn cropping system. Nonetheless, cropping system was a less influential driver of soil microbial community structure and overall C chemistry than soil type. Soil type was especially influential on fungal community structure and the chemical composition of the chloroform‐extractable C. Although plant inputs strongly influence the substrates available for decomposition and SOM formation, total C and nitrogen (N) did not differ between cropping systems within either site. We conclude this is likely due to enhanced microbial activity under the perennial cropping system. Silty soils also had a higher activity of phosphate and C liberating enzymes. After 8 years, silty loams still contained twice the total C and N as sandy loams, with no significant response to biofuel cropping system inputs. Together, these results demonstrate that initial site selection is critical to plant–microbe interactions and substantially impacts the potential for long‐term C accrual in soils under biofuel feedstock production. Abstract : Understanding controls on soil organic matter (SOM) composition is necessary to identify land management strategies that improve soil health and increase carbon (C) storage. While it is known that >50% of SOM is of microbial origin (e.g., microbial residues, degradation products of plant material), the relationships between soil microorganisms and SOM chemistry are largely unknown. We address this knowledge gap by coupling microbial characteristics with detailed SOM chemistry. We found that soil texture has a greater impact than crops on microbial communities and SOM chemistry. Our results challenge the notion that switchgrass increases C accrual in surface soils of marginal lands.